(untitled) (Bangladesh Heart Journal, 2023)
Background: Early prediction and quick diagnosis with simple, quick and easily available tool is essential part of early management of acute coronary syndrome e.g. ST segment elevated myocardial infarction. As platelet has a significant role in thrombus formation and larger sized platelets are more active in thrombotic pathogenicity, as such platelet indices can be the early predictor for acute coronary syndrome. Objective: Aim of this study was to assess the association of platelet count and mean platelet volume (MPV) in acute ST-elevated myocardial infarction. Methodology: This observational study was conducted at the department of Cardiology of National Institute of Cardiovascular Diseases (NICVD), Dhaka, Bangladesh from November 2019 to October 2020. Total 166 subjects were enrolled in this study. Among them 82 subjects (Group I) had acute ST-elevated myocardial infarction on resting ECG were admitted at CCU of NICVD and without any prior history of anti-platelet drugs intake, another 84 subjects (Group II) were enrolled in this study as control group with normal 12 lead resting ECG with normal Troponin-I. Results: No significant age difference observed between two groups (p =0.063). Significantly higher smoking and family history of coronary artery disease observed with ST elevated MI subjects (p:0.002 and <0.001 respectively). Associated risk factors like hypertension, diabetes and dyslipidemia were significantly high (<0.001) in ST-elevated MI patients. No significant difference observed in platelet count between ST elevated MI groups compared with the control (258 X 109/L vs. 267 X109/L). Mean platelet volume (MPV) was found to be higher in group I patients as compared to control (12.20±0.86 vs. 9.26±0.77) and it was significant (p <0.001). Conclusion: In acute ST-elevated myocardial infraction, higher mean platelet volume (MPV) and lower platelet count may be a useful marker. Bangladesh Heart Journal 2023; 38(2): 120-126